A 12-week lifestyle intervention: effects on fatigue, fear, and nutritional status in children with a Fontan circulation - L. E. Scheffers; L. E. Scheffers; L. E. Scheffers; L. E. Scheffers; W. A. Helbing; T. Pereira; S. Walet; E. M. W. J. Utens; E. M. W. J. Utens; E. M. W. J. Utens; K. Dulfer; L. E. van den Berg (Frontiers Media S.A., 2023)
IntroductionChildren and adolescents with a Fontan circulation are less physically active compared to healthy peers. In the current study, effects of a 12-week lifestyle intervention on fatigue, fears regarding exercise, caloric intake, rest energy expenditure (REE), and body composition were measured in children with a Fontan circulation.MethodsThis study was a semi-cross-over randomized controlled trial. The lifestyle intervention consisted of a 12-week high-weight resistance training (three supervised training sessions a week) supported by high-protein diet (>2 g/kg) and tailored recommended caloric intake. Fatigue (measured by the validated PedsQol Multidimensional Fatigue Scale), fears regarding exercise (measured on a fear thermometer), REE (measured using indirect calorimetry), caloric intake and body composition using air displacement plethysmography, and four-skinfold method were measured before and after the intervention and control period.ResultsTwenty-seven pediatric Fontan patients, median age 12.9 years (IQR: 10.5-16.2), of the included 28 patients successfully completed the program. Before training, both child- and parent-reported levels of fatigue were significantly worse on all domains (general, sleep/rest, and cognitive fatigue) compared to healthy peers. After training, parent-reported fatigue significantly improved on the general and cognitive fatigue domains [effect size +16 points (7-25), p < 0.001, and +10 points (2-17), p = 0.015, compared to the control period]. Before training, fear regarding exercise scored on the fear thermometer was low for both children and parents (median score 1 and 2, respectively, on a scale of 0-8). After training, child-reported fear decreased further compared to the control period [effect size −1.4 points (−2.3 to −0.6), p = 0.001]. At baseline, children had increased REE +12% compared to reference values, which did not change after exercise. Children ate an average of 637 calories below recommended intake based on REE, caloric deficit became smaller after the intervention, and protein intake increased compared to the control period [−388 calories (−674 to −102), p = 0.008, and +15 g (0.4-30), p = 0.044]. Body fat percentage did not change significantly.ConclusionA 12-week lifestyle intervention improved parent-reported fatigue symptoms in the children, further decreased child-reported fears, and increased caloric and protein intake.